Chlorophyll α concentration of phytoplankton during cruises of the 49th and 50th Japanese Antarctic Research Expedition in 2007-2009 - lida, Takahiro; Fukuchi, Mitsuo (National Institute of Polar Research, 2010)
P(論文) departmental bulletin paper